Visualizing an unseen enemy; mobilizing structural biology to counter COVID‐19. Issue 4 (7th April 2020) - Baker, Edward N.
Abstract : Crystallography in its broadest sense has a crucial role to play in addressing the current COVID‐19 pandemic. An outpouring of structural information on key viral proteins has resulted and importantly these data have immediately been shared with researchers round the world to speed the discovery of effective therapeutic agents. Abstract : Crystallography in its broadest sense has a crucial role to play in addressing the current COVID‐19 pandemic. An outpouring of structural information on key viral proteins has resulted and importantly these data have immediately been shared with researchers round the world to speed the discovery of effective therapeutic agents.